The genetic basis of plumage coloration and elevation adaptation in a clade of recently diverged alpine and arctic songbirds ... - Funk, Erik; Spellman, Garth; Winker, Kevin; Withrow, Jack; Ruegg, Kristen; Taylor, Scott (Dryad, 2022)
Trait genetic architecture plays an important role in the probability that variation in that trait leads to divergence and speciation. In some cases, speciation may be driven by the generation of novel phenotypes through the recombination of genes associated with traits that are important for local adaptation or sexual selection. Here, we investigate the genetic basis of three plumage color traits, and one ecological trait, breeding elevation, in a recent avian radiation, the North American rosy-finches (Leucosticte spp.). We identify unique genomic regions associated with each trait and highlight 11 candidate genes. Among these are well-characterized melanogenesis genes, including Mitf and Tyrp1, and previously reported hypoxia-related genes including Egln1. Additionally, we use mitochondrial data to date the divergence of rosy-finch clades which appear to have diverged within the past 250 ky. Given the low levels of genome-wide differentiation among rosy-finch taxa, and evidence for extensive introgression ... : DNA was extracted from a combination of tissues and blood samples. We prepared genomic libraries using a modified Nextera Protocol (Illumina, Inc.). We diluted extracted DNA to a concentration of 2.5 ng/uL followed by tagmentation of 1 uL gDNA. We indexed samples using the Nextera index kit (Illumina, Inc.) and amplified with KAPA HiFi Hot Start (Kapa Biosystems). We added primers with a reconditioning PCR and cleaned and size-selected the products using an AMPure XP bead clean-up (Agencourt). We pooled libraries for sequencing on four lanes of an Illumina HiSeq X ten, with a library fragment size targeting 350 base pairs. To map reads, we used a Dovetail-generated, chromosome-level reference genome (Dovetail Genomics, CA, USA) of a brown-capped rosy-finch (Leucosticte australis; DMNS:Bird:52416, NCBI JANIJU000000000) new to this study. We annotated genomic features using the program Liftoff (Shumate and Salzberg 2021) with the most recent zebra finch annotations that were available at the time of analysis ...